Homoeopathic Management of Hirayama Disease: A Case Report (Advancements in Homeopathic Research, 2022)
Background: Hirayama disease (HD) is a focal distal amyotrophy with unilateral or asymmetric bilateral involvement of C7, C8 and T1 innervated muscles. It affects young people with higher incidence in males with localized muscular atrophy having unilateral distribution and nonprogressive course. Case profile: A male farmer, presented with complaints of pain and numbness in upper extremities for last 20 years, severe. Complaints aggravate on exposure to cold in general, cold water and at night. It gradually leads to wasting of distal muscles of both hands, more in left hand. After detailed case-taking and repertorization, bowel nosode Sycotic Co. was given in low potency, and gradually, the potency was raised as per the response of the medicine upon patient. Discussion and Conclusion: Within 3–4 months of homoeopathic treatment, the patient started improving and improvement continued further It has been well known that conventional treatment can help relieve the complaints associated with this disease but there are chances of recurrence whereas in this case treated with individualised based on keynotes, homoeopathic medicine has brought relief in the signs and symptoms of the patient.
Keywords: Hirayama disease; Juvenile distal segment motor neuron disease disease; monomelic amyotrophy; Homoeopathy; Sycotic co.